Improving the Health-Care System in Poland - Boulhol, Hervé (OECD Publishing, 2012)
Since the transformation following the Communist era, Poland has matched improvements in health outcomes of the most developed OECD countries, although without catching up the ground lost during the 1970s and 1980s. The health status of the population remains relatively poor, although after controlling for per capita income health outcomes are only slightly below the OECD average. The Polish health-care system is characterised by low spending, a heavily regulated public system with a stringent budget constraint, restricted sub-national government autonomy and a thin private insurance market. Heavy out-of-pocket payments and long waiting lists generate inequalities in access to care. The most pressing issues to be addressed concern: easing the substantial limitations in access to care; reducing persistent inequalities; carefully designing new private health insurance; better coordinating among major public actors; improving hospital management; strengthening the gate-keeping function played by generalists; and developing a comprehensive long-term-care strategy. This Working Paper relates to the 2012 OECD Economic Review of Poland (www.oecd.org/eco/surveys/Poland)
Keywords: Social Issues/Migration/Health; Economics; Poland